Histopatologia e volume tomográfico de lesões periapicais crônicas de pacientes da Baixada Fluminense - Paixão , Fernando de Matos (2014)
1824/5000 Pulp necrosis, and consequently infection of the root canal system, stimulates an inflammatory response in the periapical region. Among chronic apical periodontitis, granulomas and differentiated cysts are distinguished only by histomorphometric analysis. The objective of the present study was the histopathological evaluation of chronic periapical lesions obtained from parendodontic surgeries, as well as the volumetric measurement of such lesions from tomographic exams prior to enucleation. Eighty biopsies collected during parendodontic surgeries performed by the UNIGRANRIO Endodontic team (CAEE No. 0072.0.317.000-10) were submitted to histological analysis of a pathologist through the standard staining of hematoxylin and eosin. Thirty CT scans, prior to enucleation and made as standard protocol for surgical planning, were evaluated for the volumetric calculation of the lesion. Multiplication of linear measurements of the panoramic, axial and transverse planes was performed through the interface of the specific software for tomographic readings Dental Slice (Brazil). Histological analysis revealed the existence of 52 granulomas (65%), 27 cysts (33.75%) and 01 periapical scar (1.25%). There was no statistically significant difference in lesion location (anterior or posterior) when compared to cysts and granulomas (p = 0.772). However, there was a statistically significant difference in the volume of lesions, obtained from tomographic images prior to surgery, when cysts and granulomas were compared (p = 0.022 / T-Student Test). According to the results obtained, the highest percentage of chronic apical periodontitis is granulomas, although the periapical cysts present greater volume from tomographic exams.